2021
DOI: 10.7759/cureus.15717
|View full text |Cite
|
Sign up to set email alerts
|

Possible Vertical Transmission From an Unsuspected SARS-CoV-2-Infected Mother to Her Newborn

Abstract: Although the Coronavirus Disease 2019 (COVID-19) has been found to have multiple routes of transmission, limited data exist on whether the vertical transmission of severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) can occur from asymptomatic infected mothers to their newborns during pregnancy. We report a full-term newborn girl who was found to be positive for COVID-19 at 24 hours of life and subsequently symptomatic with fever, tachycardia, tachypnea, elevated lactate dehydrogenase, and elevated to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 18 publications
(22 reference statements)
1
5
0
Order By: Relevance
“…Consequently, in Japan, as in other countries worldwide, vaccination with the BNT162b2 XBB.1.5 vaccine, which is compatible with the omicron SARS-CoV-2 spike glycoprotein, is recommended (19). In line with these recommendations, we have similarly shown that pregnant women vaccinated with BNT162b2 XBB.1.5 exhibit the transfer of neutralizing antibodies (IgG and IgA) against the spike glycoprotein of SARS-CoV-2 to umbilical cord blood and breast milk (10,13,14,15).…”
Section: Discussionsupporting
confidence: 66%
See 1 more Smart Citation
“…Consequently, in Japan, as in other countries worldwide, vaccination with the BNT162b2 XBB.1.5 vaccine, which is compatible with the omicron SARS-CoV-2 spike glycoprotein, is recommended (19). In line with these recommendations, we have similarly shown that pregnant women vaccinated with BNT162b2 XBB.1.5 exhibit the transfer of neutralizing antibodies (IgG and IgA) against the spike glycoprotein of SARS-CoV-2 to umbilical cord blood and breast milk (10,13,14,15).…”
Section: Discussionsupporting
confidence: 66%
“…A clinical study revealed the presence of neutralizing antibodies against the spike glycoprotein of SARS-CoV-2 in umbilical cord blood and breast milk of pregnant women vaccinated with the mRNA-based COVID-19 vaccine (BNT162b2) (10,11,12,13,14,15). However, the amino acids in the spike glycoprotein of SARS-CoV-2 mutate rapidly (16), leading to the emergence of numerous mutant viruses and their subvariants of SARS-CoV-2.…”
Section: Discussionmentioning
confidence: 99%
“…This observation was also reported by several studies; however, most of the infected neonates were only mild during the prenatal period 31 , 32 . Furthermore, a previous case report presented a pregnant woman without unsuspected COVID-19 symptoms delivered a fetus with COVID-19 typical symptoms and confirmed positive PCR test, which demonstrates that vertical transmission can highly occur during the late pregnancy (3rd trimester) or upon delivery even if the mother have non-specific symptoms of COVID-19 33 . This case spotlights the value of regular COVID-19 screening of pregnant women for specific and nonspecific symptoms of the disease prior delivery to account all required precautions and ensure safety of mothers, newborns, as well as medical staff.…”
Section: Discussionmentioning
confidence: 75%
“…A clinical study revealed the presence of neutralizing antibodies against the spike glycoprotein of SARS-CoV-2 in umbilical cord blood and breast milk from pregnant women vaccinated with the mRNA-based COVID-19 vaccine (BNT162b2) [ 13 , 14 , 15 , 16 , 17 , 18 ]. However, the spike glycoprotein of SARS-CoV-2 undergoes rapid mutations [ 19 ], leading to the emergence of numerous mutant viruses and their subvariants.…”
Section: Discussionmentioning
confidence: 99%